Teaching Spoken Narrative Text by Using Animation Film to Junior High School Students - Irena Putri; Aryuliva Adnan (Journal of English Language Teaching, 2019)
This article aims to explain how animation film can increase students’ motivation in learning spoken narrative text. Animation film is used as a media in teaching spoken narrative text to increase students’ motivation in learning spoken narrative. Animation film is chosen as a media in teaching spoken narrative text because it is familiar to Junior High School students. Students will be more interested and motivated to study if learning process is done by doing fun activities.  In addition, animation film gives them a guidelines about what they want to tell. As an audio visual media, it enable students to understand the story through sight and sounds. Then, animation film also facilitates students to memorize the events in sequence. By using animation film to teach spoken narrative text, students will be easier to understand the story and can tell the story well.